États du futurisme dans l’anticipation et la science-fiction (et leurs fins du monde) - Irène Langlet (Belphégor)
The end of the world is not a recent theme in anticipation literature. They even experienced several vogues between 1860 and 1940, at the very moment when, according to François Hartog (and according to Reinhardt Koselleck, whose hypotheses the former follows), the regime of futuristic historicity became dominant in the West. How shall we understand this contradiction? Is this a foreshadowing of the escheat of the future which paralyzes our Zeitgeist, a hundred years later? One might think that the march towards future was only an illusion, carried by inherently false genre fictions. But we can also argue that science fiction, and the anticipation literature that comes earlier in the literary history of modernity, are characterized by a hybridization of different regimes of historicity, which radically complicate the issue of the ends of the world. In their meta-narrative as well as in their forms and practices, the ambivalences of genre fictions highlight at best the cultures of the future in the West.